'Curui': weaving climate justice and gender equality into Fijian educational policies and practices - Lagi, R; Waqailiti, L; Raisele, K; Sanchez Tyson, L; Nussey, C (Taylro and Francis, 2023)
This paper takes inspiration from the Indigenous Fijian practice of ‘curui’ – weaving or patching together – as a metaphor to explore connections between climate justice, gender equality, and education in Fijian policies and practices. The paper argues that neither gender equality nor education can be ‘silver bullets’ for the huge challenges that the climate crisis raises, particularly for small island developing states (SIDS) such as Fiji that exist at the sharp end of the crisis. The paper contributes close analysis of Fijian national climate change policies and development plans from 2010, identifying the ways in which these policies frame and discuss the connections between climate, gender, and education, and asking whether these policies acknowledge traditional ecological knowledges, and the extent to which they are aligned with notions of justice. It argues that connected approaches to education, centred in Indigenous knowledges and ontologies, have thus far been insufficiently included in Fiji’s policies.